Minimizing Cholesterol-Induced Aggregation of Membrane-Interacting DNA Origami Nanostructures - Jasleen Kaur Daljit Singh; Minh Tri Luu; Jonathan F. Berengut; Ali Abbas; Matthew A. B. Baker; Shelley F. J. Wickham (Membranes, 2021)
DNA nanotechnology provides methods for building custom membrane-interacting nanostructures with diverse functions, such as shaping membranes, tethering defined numbers of membrane proteins, and transmembrane nanopores. The modification of DNA nanostructures with hydrophobic groups, such as cholesterol, is required to facilitate membrane interactions. However, cholesterol-induced aggregation of DNA origami nanostructures remains a challenge. Aggregation can result in reduced assembly yield, defective structures, and the inhibition of membrane interaction. Here, we quantify the assembly yield of two cholesterol-modified DNA origami nanostructures: a 2D DNA origami tile (DOT) and a 3D DNA origami barrel (DOB), by gel electrophoresis. We found that the DOT assembly yield (relative to the no cholesterol control) could be maximised by reducing the number of cholesterols from 6 to 1 (2 ± 0.2% to 100 ± 2%), optimising the separation between adjacent cholesterols (64 ± 26% to 78 ± 30%), decreasing spacer length (38 ± 20% to 95 ± 5%), and using protective ssDNA 10T overhangs (38 ± 20% to 87 ± 6%). Two-step folding protocols for the DOB, where cholesterol strands are added in a second step, did not improve the yield. Detergent improved the yield of distal cholesterol configurations (26 ± 22% to 92 ± 12%), but samples re-aggregated after detergent removal (74 ± 3%). Finally, we confirmed functional membrane binding of the cholesterol-modified nanostructures. These findings provide fundamental guidelines to reducing the cholesterol-induced aggregation of membrane-interacting 2D and 3D DNA origami nanostructures, improving the yield of well-formed structures to facilitate future applications in nanomedicine and biophysics.